Il bisogno dei valori e ricerca del senso della vita dei giovani di oggi. Punti Chiavi della Logoterapia di Viktor E. Frankl applicati nel campo formativo - Michał Styczyński (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
During their existence, people often forget about the meaning of life. With the world spinning faster and faster, the disappearing ability to reflect on complex day-to- day life, the virtual reality and ‘the net’ jungle, people are forgetting how to discover values that lead to the higher goal. There is special concern for the young generation which often loses the meaning of life. The answer to the question – how to find the meaning of life – gives the theory of logotherapy and existential analysis, which was created by Victor E. Frankl. The story of his life, and the difficult experiences which led him to discover the meaning of life persuade the reader about the truthfulness of his scientific discoveries. Logotherapy is a way to find goals and meaning in life: it makes people think about their existence. Frankl shows a certain hierarchy of values, which appear during specific and often difficult life situations. He survived four concentration camps and during those extreme times he was able to find meaning in life. What is more, he helped others find their meaning. A teacher appears on a young man’s life path and this teacher, according to logotherapy, should become the logo-educator and witness to the values. He should be someone, who points to meaning and is able to manifest the meaning of his own existence. Through a mature relationship with the student, the teacher helps the student discover what is the most important. The teacher helps the student realise one’s own plans through to the will, meaning and human conscience – spaces through which the sens consciousness shines through.